Comparison of distress in breast cancer survivors treated with different adjuvant endocrine therapies: a single-centre cross-sectional study. Issue 3 (3rd July 2017) - Kus, Tulay; Aktas, Gokmen; Ekici, Hatice; Elboga, Gulcin
ABSTRACT: AIM: To compare the depression and anxiety scores among breast cancer (BC) survivors who received different adjuvant endocrine therapies. PATIENTS AND METHOD: A total of 154 patients (with 6 months to 10 years follow-up) were recruited in this cross-sectional study. The patients were divided into three groups according to the type of endocrine therapy: selective oestrogen receptor modulator (tamoxifen), third-generation aromatase inhibitors (AIs; e.g. anastrozole and letrozole), and luteinizing hormone realizing hormone (LHRH) analogue with tamoxifen. Patients' age, menopausal status at diagnosis, educational level, marital status, and disease characteristics including stage, treatment, and follow-up period since diagnosis were noted. Beck Depression Inventory, Beck Anxiety Inventory, and Duke-University of North Carolina Functional Social Support Questionnaire were used to assess the depression, anxiety, and functional social support, respectively. Statistical significance of the associations was analysed using Spearman correlation, Student's t, Mann–Whitney u, and ANOVA tests. RESULTS: Patients' mean age was 49.8 (28–77) years. Age and perceived social support which are patient-related factors affected anxiety and depression scores, while disease-related factors did not affect. Patients who received LHRH analogue with tamoxifen presented more anxiety scores. Patients who received tamoxifen had more depression scores than those who received AIs. This may have been due to the fact that the tamoxifen group is composed of young and pre-menopausal patients. CONCLUSION: Young age and lower social support are important determinants of higher anxiety and depression scores. The use of LHRH analogue is one of the risk factors for the development of anxiety in BC survivors.